Candida albicans aspects of novel silane system–coated titanium and zirconia implant surfaces. Issue 3 (23rd January 2014) - Villard, Nicolas; Seneviratne, Chaminda; Tsoi, James Kit Hon; Heinonen, Markku; Matinlinna, Jukka
Abstract Objectives The aim of the present study was to evaluate the effect of novel silane system coatings on zirconia and titanium implant surfaces and the attachment of the fungal pathogen Candida albicans. Materials and methods Titanium and zirconia specimens were silica‐coated and silanized either with a commercial silane primer (RelyX Ceramic Primer™, 3M ESPE) or a novel silane system primer. The novel silane system primer was a blend of 1.0 vol% 3‐acryloxypropyltrimethoxysilane and 0.3 vol% bis‐1, 2‐(triethoxysilyl)ethane diluted in acidified ethanol‐water solvent. The surface roughness (Ra), the surface free energy and the chemical composition of substrate surfaces after treatments were evaluated. C. albcans biofilms were developed on silica‐coated + silanized surfaces during 48 h of incubation time. Colony forming units (CFU) and real‐time PCR (RT‐PCR) quantified the cells on the material surfaces. Statistical analyses were carried out by 1‐way ANOVA, Tukey post hoc and Games Howell post hoc test at 5% significance level (p). Results On zirconia and titanium surfaces, the Ra and the chemical composition of the specimens were equal (P < 0.05). The surface free energy was decreased on titanium specimens and increased on zirconia specimen after silanization. CFU of C. albicans was significantly lower on zirconia coated with RelyX Ceramic Primer™, (P < 0.001) and on titanium coated with both silanes (P = 0.002). RT‐PCR revealed no differences between the mean quantities of C. albicans (P ≥ 0.067). Conclusion Silica‐coating and silanization had modified the titanium and zirconia surfaces significantly. Both the control and experimental silane primers might inhibit the biofilm formation of C. albicans.